2010
DOI: 10.26719/2010.16.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of lung cancer cases in Qatar

Abstract: This study documents for the first time the clinical and epidemiological characteristics of lung cancer cases in Qatar from 1998 to 2005. The age-standardized incidence rate was higher than that in many other Gulf countries: 8.95 per 100 000 (15.2 per 100 000 for males; 3.95 per 100 000 for females). Mean age at diagnosis was 57.5 years. Most patients were current smokers or ex-smokers at the time of diagnosis (82.5%). Unlike other Gulf countries, adenocarcinoma was the predominant type in both Qatari national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…A study conducted in Syria reported an average age at starting shisha smoking of respectively 19 and 21 years among males and females, 23 suggesting that shisha smokers have similar characteristics, regardless of country of residence. As with other studies, 3,7,21,22 we noted an increase in shisha smoking among females compared with cigarette smoking. This may reflect the social acceptance of this kind of tobacco use.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study conducted in Syria reported an average age at starting shisha smoking of respectively 19 and 21 years among males and females, 23 suggesting that shisha smokers have similar characteristics, regardless of country of residence. As with other studies, 3,7,21,22 we noted an increase in shisha smoking among females compared with cigarette smoking. This may reflect the social acceptance of this kind of tobacco use.…”
Section: Discussionsupporting
confidence: 91%
“…T obacco smoking has been well-recognised as a leading preventable cause of morbidity and premature mortality worldwide. [1][2][3][4] According to the World Health Organization (WHO), tobacco kills at least 6 million people each year, and the number is expected to rise to 8 million by 2030. 5 The prevalence of tobacco smoking in the form of cigarettes is generally declining, while waterpipe (also known as shisha) smoking is on the rise.…”
mentioning
confidence: 99%
“…Furthermore, smoking-related diseases are the most prevalent in Qatar. Ischemic heart disease, as an example, was ranked as one of the leading causes of burden of disease in Qatar in 2010 [ 32 ], and Qatar has a higher age standardized lung cancer incidence rate than many countries in the Gulf (8.95 per 100,000) [ 33 ]. In addition, according to a recent survey done by Weill Cornell Medical College in Qatar, at least 1 billion cigarettes are smoked in Qatar each year, averaging 12,000 per individual, and 65 million US dollars (USD) are spent on cigarettes annually; 150 million USD are used to cover the healthcare costs of patients affected by smoking-related diseases [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, tobacco smoke associated with many types of cancer, it is linked primarily to lung cancer in 90% of men and 70–80% of lung cancer in women ( 4 ). Furthermore, tobacco smoke causes more than 13 types of cancer in men and women ( 5 – 11 ). The main consequences of long-term exposure to tobacco smoke associated with the premalignancy mechanism, which is a considerably delayed process, sometimes taking several years ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…These health issues require sophisticated genomic assays besides the clinical procedures ( 14 16 ). The incidence of disease and cancer risks from cigarette smoking among male and female smokers, increased in the Middle East and worldwide over most of the twentieth century, and continued in the twenty-first century as compared with persons who have never smoked ( 5 , 6 , 17 19 ).…”
Section: Introductionmentioning
confidence: 99%